PLASTIC BAG WRAP FOR PREVENTION OF HYPOTHERMIA IN PRETERM AND LOW-BIRTH WEIGHT INFANTS - Dian Ramawati; Hikmi Muharromah Pratiwi; Candra Andodo (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Hypothermia is low-body temperature (less than 36,5°C) that can caused morbidity and mortality in premature newborn and or low-birth weight newborn. Plastic has often been used to prevent the heat loss in newborn.The aim of study was to measure the effectiveness of plastic bag wrap to prevent hypothermia in preterm and low-birth weight infant. Method. The study design was quasy expertment non randomized pretest-posttest with control group. In intervention group, there were five premature and or low-birth weight newborns that were being wrapped with special design plastic bag from neck to toe after been given neonatal standard care protocol. While, in control group, there were six newborns with the same baseline criteria as intervention group without plastic bag wrap. The measurement of body temperature used digital thermometer on babies’ axilla before and after one-hour intervention. Data analysis used t test. Result. The result showed there was almost significant difference in body temperature in newborn before and after intervention (pvalue 0.056). Discussion. Plastic bag wrap is effective to prevent hypothermia in premature and or low-birth weight newborn as much as 60% with body temperatur changes +0.4°C. Keywords: Plastic Bag Wrap, Hypothermia, Preterm, Low-Birth weight